“Jika Diedukasi, Kami Siap”: Perspektif Kesiapan Pokdarwis Dalam Kesehatan Jiwa Berbasis Pariwisata - Shofi Khaqul Ilmy; Made Bayu Oka Widiarta; I Komang Gunawan Landra; Kadek Dwi Pitriyani; I Gusti Ayu Armadhira Iswa Adi (Optimal Nursing Journal, 2025)
Introduction: Local tourism has the potential to serve as a platform for mental-health promotion and prevention; however, the readiness of community actors-particularly tourism awareness groups (Pokdarwis)-remains poorly understood. This study aimed to explore Pokdarwis members’ perceptions and meanings of readiness to advance mental-health efforts through local tourism in Buleleng District, Bali. Methods: A qualitative descriptive phenomenology was conducted with seven Pokdarwis members (including two coordinators) through semi-structured interviews. Data were analyzed using Template Analysis, treating the Community Readiness Model (CRM) as sensitizing concepts (prior knowledge). Trustworthiness was ensured via member checking, peer debriefing, and an audit trail. Results: Six themes emerged: (1) meanings of health along the mental-health dimension (knowledge of the issue); (2) a “quiet yet important” issue (community climate); (3) abundant but unguided potential (existing community efforts); (4) mental-health benefits that remain unpublicized (knowledge of efforts); (5) “If educated, we are ready” (leadership); and (6) potential that is not yet connected (resources). A core theme was synthesized, conditional readiness: “If educated, we are ready.” CRM mapping indicated a position spanning vague awareness to preplanning. Discussion/Recommendations: Stage-matched priorities include strengthening culturally sensitive mental-health literacy; reframing destination narratives toward “restorative tourism”; appointing and training relevant actors; piloting small-scale packages with clear standard operating procedures and referral pathways; and consolidating assets-networks-funding. Community mental-health nurses should act as key collaborators linking Pokdarwis and puskesmas (primary health centers) to support standardization, capacity building, and ongoing quality monitoring of the program.